Process Of Egg Salt Smoke In Htm Jaya Brebes - Hanna Rizqi Nurbaety; Nurwati Nurwati (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2021)
Local ducks in Indonesia are generally kept as one of the egg producers. This study aims to determine the processing of salted smoked eggs in HTM Jaya. This research was conducted in HTM Jaya which is engaged in processing salted eggs for 30 days. The approach used is a qualitative approach, so that the researcher can describe all events during the research process. The data sources used are primary data and secondary data. Raw materials for duck eggs are obtained from two places, namely the pesantunan village and the jatibarang village. the incubation time is 12 days. The smoking is carried out for 4-6 hours with hot coals (coconut shell charcoal) which must always burn stably. Packaging is done after the eggs are smoked and aerated until warm. Packaging is done using a box, the reason for using a box is because it is more practical and affordable. In each box package there are 10 eggs